100 years of wellcome - an unusual company celebrates its centenary - Editorial Office (AOSIS, 1980)
Not many companies are owned by a charitable trust or have a Nobel Prize winner amongst their research scientists. These are two of the unusual features of the Wellcome Foundation, which celebrates its centenary this year. Wellcome is owned by the Wellcome Trust, a charitable organisation which utilises all money made out of the company's operations in relief of suffering and disease, to further the relief of suffering and disease.